Pengaruh Problem Based Learning Terhadap Metakognisi dan Hasil Belajar Materi Pencemaran Lingkungan - Dian Priyanti; Rini Rita T. Marpaung; Arwin Achmad (Universitas Lampung, 2018)
This research aims was to determine the effect of PBL on metacognition skills and learning outcomes. The design was a nonequivalent pretest-posttest control group design. The research sample were the students of VIIA and VIIC amounted of 60 students that were selected through cluster random sampling technique. Data on metacognition skills wereobtained from questionnaires and data on learning outcomes obtained from pretest and posttest. Data on metacognition skills were analyzed descriptively while learning outcomes were analyzed by Independent Sample t-Test at 5% confidence level. The results showed that the experimental class metacognition skills were higher with the criteria of